(untitled) (European Journal of Pure and Applied Mathematics, 2023)
Our goal in this paper is to generalize the integral transforms and use it with He’s polynomial method to find the solution of the nonlinear partial differential equations. All results of theoretical studies regarding the generalization and its properties are presented. For the He’s polynomial method, it is used to solve the nonlinear part of the partial differential equation. It is shown that the importance of my research is the combination of generalization of integral transforms with He’s polynomial method allows for exact and approximate solutions configurations to be determined. Furthermore, the generalization of integral transforms has been shown to include most, or even all, of the integral transforms and be applicable to a variety of equations, making it a crucial tool in solving them. Finally, the capability of solutions to be obtained quickly and easily through this combined technique provides an invaluable tool for solving problems.